Timing of Breakup and Thermal Evolution of a Pre‐Caledonian Neoproterozoic Exhumed Magma‐Rich Rifted Margin. Issue 6 (5th June 2019) - Kjøll, Hans Jørgen; Andersen, Torgeir B.; Corfu, Fernando; Labrousse, Loic; Tegner, Christian; Abdelmalak, Mohamed Mansour; Planke, Sverre
Abstract: During the terminal stages of Wilson cycles, remnants of magma‐poor margins may be incorporated into the orogens, whereas the magma‐rich margins often are lost in subduction due to low buoyancy. The understanding of magma‐rich margins is therefore mostly based on drill holes and geophysical observations. In this contribution, we explore the temporal evolution and the ambient conditions of a magma‐rich rifted margin preserved within the Scandinavian Caledonides. The Scandinavian Dike Complex was emplaced into a sedimentary basin during the initial breakup and opening of the Iapetus Ocean 615 to 590 million years ago. The dike complex constitutes 70–90% of the magma‐rich, syn‐rift basins and is locally well preserved despite the complex Caledonian history. This contribution provides new observations about the geometry, relative timing, and development of the margin. Jadeite‐in‐clinopyroxene geothermobarometry, titanium‐in‐biotite geothermometry, and garnet isopleth modeling show that the ambient pressure and temperature conditions were similar for the entire dike complex at 0.25 to 0.45 GPa, with contact metamorphic temperatures up to approximately 700 °C. In the northernmost part of the study area, U‐Pb dating of magmatic zircon shows that partial melting of the sedimentary host rock, at relatively shallow levels, occurred at 612 Ma. This shows that the crust was molten already 6 million years before the northernmost dike swarm was emplaced at 605.7 ± 1.8 Ma. We propose that the locally pervasive partial melting occurred due to high geothermal gradients and introduction of mafic melt in the lower crust. These processes significantly reduced the strength of the crust, eventually facilitating continental breakup. Plain Language Summary: This project investigates what the crust looks like and how it behaves when continents are rifting and finally break apart to form a new ocean. Sometimes the breakup is associated with magmatism. When this is the case the structure and behavior of the crust change dramatically from their state when no magma is involved. One important implication is that the heat brought by the magma presumably makes the crust very hot and weak and thus easier to break. Direct observations of magma‐rich rifted margins are sparse, but in an area of Scandinavia, the deep parts of a rift in the Earth's crust have been preserved and exposed through complex geological processes. The study of these rocks reveals the processes that were active at depth when the continents broke apart. We have used mineral chemistry and age dating to show that the studied areas formed at approximately 9‐ to 16‐km depth more than 600 million years ago. Our observations indicate that the stretching started when the crust was relatively cold, possibly causing earthquakes. Later, the crust was heated by magma intrusions to such a degree that it started to melt and became very weak, which made it easier to stretch and break the continent apart. Key Points: Detailed field observations reveal crustal structures of a well‐preserved exhumed magma‐rich rifted margin in the Scandinavian Caledonides The dike swarm was emplaced at 9‐ to 16‐km depth and introduced significant amounts of heat into the crust causing local crustal anatexis U‐Pb dating shows that these processes occurred between about 615 and 590 Ma